A Task-Based Analysis of Undergraduate Assessment: A Tool for the EAP Practitioner - Dunworth, Katie (Teachers of English to Speakers of Other Languages, Inc, 2008)
Within the field of English for academic purposes (EAP), one issue that attracts consensus in the literature is the importance of needs analysis. As Benesch (2001) observes, “needs analysis offers detailed information about the linguistic and cognitive challenges students face in academic settings” (p. 61). Although there is rather less unanimity on what those needs might be—see, for example, Pennycook’s (1997) critique of vulgar pragmatism—all approaches nevertheless accept certain fundamentals. One fundamental is the need for EAP teachers to be aware of the discourse types that occur in the domains to which EAP students will progress. However, it is not always a straightforward matter to determine what these discourse types might be. Thus it is necessary for EAP tutors or curriculum designers to be familiar with the work that their students, who may be from a range of discipline areas, will be required to do. Certainly numerous studies have been conducted into specific, and usually written, academic genres, particularly at the graduate level, but there is a paucity of widely available information on the complete range of tasks that undergraduates are required to undertake. This brief report summarises an empirical study that identified the range of tasks undertaken by neophyte undergraduate students and thereby provides EAP practitioners with information for their ongoing efforts to design programs.